Sistem Tata Kelola Kearsipan di Kantor Kepala Desa - Nurul Laili Herzegovina, Rani; Mokhamad Saiful Hasan (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2023)
Klanting Village is one of the villages in Indonesia's East Java province's Sukodono sub-district, Lumajang Regency. Villages in the Lumajang Regency are included within the borders of Klanting Village. Farm laborers, domestic helpers, breeders, civil servants, and other laborers are the most in-demand jobs in Klanting Village. The Klanting Village Office served as a model for this article because of its nearly identical issues with archival administration. The goal of this study was to identify the challenges the village government encountered in running the village archives. A qualitative research approach was adopted, and it is descriptively reported. The two stages of observation and interview with village employees who manage archives were used to get the data. Additionally, information was gathered through document and literature studies, specifically through books on archives, laws governing archives, and regulations governing archives. The stages of data reduction, data presentation, and conclusion or verification make up the data analysis procedure used in this study. The study's findings indicate that, despite the fact that it is not ideal, village archives are generally managed well. This is due to a number of factors, including a dearth of village employees with the necessary skills and knowledge to handle archives, a lack of facilities and infrastructure, and a lack of funding for archive management. The purpose of this research is to inform the village about effective archival management, which will help village governance and enhance community services.